YOUTH WORK PRACTICE THROUGH ADVERTISING: A MULTIMODAL CRITICAL DISCOURSE ANALYSIS - Media Febriana Sulistyan; Muhammad Aras; Intansari Putriani; Febyanti Syafitri Hartono (Ikatan Dosen Menulis, 2023)
This article aims to examine the discourse on the practice of youth workers in Indonesia, constructed by commercial advertisements for A-mild cigarettes on television and social media, using semiotics multimodal critical discourse analysis research method. This article will analyze the ability of advertising communication to criticize several influential parties in young people's work practices. The commercial advertisement produced by A-mild shows how the younger generation works and how the relationship between young workers and their seniors; the result is that there are three views about the work practices of young people, namely (1) young workers are a multitasking generation, (2) productivity of young workers will be optimal if under the supervision and appreciation of experienced professionals, and (3) senior distrust of the abilities of young people is because they prioritize interpersonal relationships that have been established.